Evaluación del efecto de la permeabilidad en el diseño y mecanismos de propagación de las fracturas hidráulicas mediante simulación numérica (2021)
Initially, an analysis of the petrophysical and mechanical properties of the formations of interest was elaborated, in addition to the pumping programs taking into account the injection rates, description of the propant and fracture fluid based on the closure stress. Subsequently, Log-Log, G-Function and Square Root graphs were constructed where the Minifrac parameters were reported, such as Leakoff mechanism, fracture closure pressure, net pressure at fracture closure, fluid efficiency and fracture closure time. . After these results, a pressure matching was developed that allows comparing the observed net pressure and the modeled net pressure.